Security assurance of port services as a factor of their competitiveness - Kirillova, Elena; Makushev, Petr; Perepichko, Maiia; Piterska, Varvara; Raskevych, Igor (Technology audit and production reserves, 2019)
The object of research is the process of increasing the competitiveness of ports. One of the most problematic places is the endlessness of the services provided by ports, which affects the competitiveness of ports. The methods for quantitative assessment of the possibility of reliable delivery, methods for calculating the parameters of the infrastructure and superstructure of ports, solution methods using the theory of mass service are used. The analysis of research and the work of international organizations on the determination of factors by the clientele of ports are carried out, given the change of priorities in favor of the reliability of the service. Ports today are considered in this sense as nodes in logistics chains. Under the conditions by which supply chains are developed, evaluated and selected, reliability is given priority over the price and transit time. It is determined that the ability of ports to ensure the reliability of the service should be considered from the perspective of creating the appropriate capacities as part of the infrastructure and port superstructure, as well as labor resources. For each element (berths, warehouses, equipment, dockers) it is determined in the selected tested methods, due to which reliability is ensured. So, the required number of berths is determined taking into account their annual throughput, which is justified taking into account the coefficient of berth utilization in time, the use of which allows ensuring the reliability of the availability of the required number of berths. The reliability of the availability of the necessary storage capacity is determined from the conditions for ensuring uninterrupted fleet processing. The necessary composition of transshipment equipment depends on the processing conditions of the fleet. Reliability in providing labor resources can be ensured by taking into account the peculiarities of the organization of labor in ports associated with irregular demand for workers due to intermittent and unpredictable arrival of ships and cargo at the port. The definition of favorable port cargo flows, taking into account additional sales and customer loyalty, and an efficiency criterion, the task of determining the number of dockers, segmentation of ship –owners, is proposed. As a result, a scientific and methodological product is developed suitable for use as suppliers and customers of cargo delivery services.